FRUCTOSE ALTERS THE EXPRESSION OF TYPE B LEPTIN RECEPTOR IN HYPHOTALAMUS AND INTESTINUM OF Rattus Novergicus - Rachmawati, Ermin; Kristanti, Risma Aprinda; Susanti, Nurlaili (Journal of Islamic Medicine, 2018)
Background: Several epidemiological dataâ€™s reported significant correlation between fructose consumption and diabetes mellitus type 2 by inducing insulin resistance. Leptin resistance induced by fructose was proposed as one novel mechanism that induce insulin resistance but the exact mechanism remains unclear. Â We hypothesize that fructose diminish the type b leptin receptors in hypothalamus and intestine.Aim: This study was aimed to elucidate fructose effect on the expression of leptin receptor type b in hypothalamus and intestine of Rattus novergicus.Method: twenty eight rats were used and divided into 4 groups: Group 1 was control, group 2 was given fructose 10%, group 3 was given fructose 30% and group 4 was given fructose 55% for 2 months. At the end of treatment, the animal were sacrificed and then the hypothalamus and intestine were collected. The expression of type b leptin receptor were measured by immunohistochemistry technique with primary antibody from Bioss antibodies type Leptin receptor polyclonal antibody bs-0109R using Staining kit Skytec Laboratories and DAB chromogen. A positive expression can be seen as a brown colour in cell cytoplasm and counted in 100 cell. The expression then analysed using SPSS 18 with anova one way tes (p0,05) followed by post hoc test after the data showed normality and homogeneity using Saphiro wilk and Levene test (p0,05).Result: There was significant differences in type b leptin receptors found in hypothalamus between each group (p0.05). The significant differences also could be seen in the expression between control and group fructose 30 and 50% in intestinal cell (p0.05).Conclusion: the consumption of Fructose 55% for 2 months attenuates the expression of type b leptin receptors in hypothalamus and intestine of Rat novergicus.Â